Epigenetically mediated gene silencing: a companion to genetic alterations in driving tumorigenesis - Baylin, Stephen (Henry Stewart Talks, 2007)
Introduction to epigenetic changes in cancer, defining the process of promoter DNA hypermethylation as a constituent of a broad range of chromatin abnormalities in cancer, defining the genes aberrantly silenced in cancer including approaches being used to screen the cancer genome for such genes, defining what is known about the interaction of DNA methylation and chromatin modifications for initiating and maintaining gene silencing in cancer, outlining the position of aberrant gene silencing in tumor progression and particularly highlighting the key role these changes may play for the earliest steps in tumorigenesis, defining the potential for using DNA hypermethylated gene promoter sequences as molecular markers for cancer risk assessment, early diagnosis and prognosis, discussing the possibilities for targeting reversal of gene silencing as a prevention and therapeutic strategy for cancer
Archived at 2018/12/10